Perbedaan Hasil Belajar Menggunakan Metode Round Robin dan Metode Diskusi terhadap Pembelajaran Ekonomi Kelas X IPS SMA Negeri 2 Bukittinggi TP. 2017/ 2018 - Sefrian Rahmanda (Universitas Negeri Padang, 2018)
This reserch intent to analyst diferent result study Economic student that use method Round Robin and method discussion. This reserch do in SMA N 2 Bukittinggi. For to get data and information in this reserch, writer perform experiment in 2 sample class. Type data for reserch is data prime and data sekunder. Technique analyst data that is descriptive and induktive with use Z test before that normality test and homogenity test must use to 2 sample class. Result of reserch indikation mean value Round Robin class 65,063 and discussion class 62,303. Result Z test is 1,96 with α 0,05. Therefore Zhitung < Ztab then H0 reject, with that there no diferent that signifikant for result study Economic student with method Round Robin and Method diskusiKeyWord: Round Robin, Discussion, resut sudy